Tectonic Fabric, Geochemistry, and Zircon-Monazite Geochronology as Proxies to Date an Orogeny: Example of South Delhi Orogeny, NW India, and Implications for East Gondwana Tectonics - Singh, Subhash; De Waele, Bert; Shukla, Anjali; Umasankar, B. H.; Biswal, Tapas Kumar (Frontiers in Earth Science, 2021)
We have dated the South Delhi orogeny, Aravalli- Delhi Mobile Belt, NW India, using blastesis-deformation relationships. geochemistry and zircon- monazite geochronology as proxies. The South Delhi Terrane, a passive margin domain in the mobile belt, is characterized by multiply deformed (D1-D4) greenschist facies rocks and several granite plutons. The D1 deformation produced a pervasive tectonic fabric, S1, axial planar to a set of isoclinal -recumbent F1 folds in all rock types. The S1- minerals grew under peak greenschist facies metamorphism, M1, during the D1 phase. The age of D1 is constrained by the syncollisional peralkaline- S type Sewariya granite that is characterized by a magmatic/ submagmatic fabric (Sm) coplanar with S1. The margin of the pluton is sheared into a gneiss under high-temperature deformation. The zircon geochronology of the Sewariya granite gives an age of D1 at ca. 878 Ma. The monazite geochronology of the mica schist constrains M1 at ca. 865- 846 Ma. The other granite plutons and metarhyolite are pre-D1 and emplaced at ca. 992-946 Ma. The D2 deformation produced NE-SW trending open upright F2 folds coaxial with F1 and northwesterly vergence thrusts axial planar to F2. Monazite geochronology constrains D2 at ca. 811-680 Ma. D3 produced NW-SE trending folds. The D4 phase created faults and fractures marking the brittle deformation in the rocks, which are constrained at ca. 588-564 Ma. There are upper amphibolitic tectonic slivers along the Phulad thrust belonging to pre- Delhi rocks that show a ca. 1638 Ma metamorphism age. From the above study, it is suggested that the South Delhi orogeny formed at ca. 878- 680 Ma, marking the final amalgamation of Marwar Craton with the rest of India. This overlaps the early phase of the Pan-African orogeny (900-630 Ma). The brittle deformation, D4, coincides with the Kuunga orogeny (650 -500 Ma). Our study implies that India, like other continents in the East Gondwana, underwent amalgamation of internal blocks until the later Neoproterozoic.